Evaluation of National Comprehensive Cancer Network guideline‐based Tool for Risk Assessment for breast and ovarian Cancer (N‐TRAC): A patient‐reported survey for genetic high‐risk assessment for breast and ovarian cancers in women. Issue 3 (21st January 2019) - Ozanne, Elissa M.; Howe, Rebecca; Mallinson, David; Esserman, Laura; van't Veer, Laura J.; Kaplan, Celia P.
Abstract: Identification of mutations that increase lifetime risk of breast and ovarian cancer is critical to improving women's health. Because these mutations are relatively rare in the general population, there is a need for efficient methods to identify appropriate women to undergo genetic testing. The objective of this study was to assess the feasibility, accuracy, and performance of theN CCN guideline‐basedT ool forR iskA ssessment for breast and ovarianC ancer (N‐TRAC)—a patient‐facing assessment for those affected and unaffected by cancer. This study enrolled a prospective cohort of 100 affected and 100 unaffected women that used N‐TRAC in a clinical setting. Recommendations for referral to genetic counseling based on N‐TRAC and other standard risk assessment methods were compared . Seventy‐seven of the 100 affected women and 35 of the 100 unaffected women were identified as high risk by N‐TRAC. The average completion time was approximately 2 min for both groups. N‐TRAC accuracy for family history was exceptional in both groups (kappa > 0.96). N‐TRAC and other risk assessment methods do not always identify the same high risk population. N‐TRAC is an accurate and feasible tool that can assist in identifying women at increased risk for hereditary breast and ovarian cancer and may lead to more informed decision‐making.